Stages of atherosclerotic plaque development and unstable plaque types: pathophysiologic and histologic characteristics - Yu. I. Ragino; A. M. Volkov; A. M. Chernyavskyi (Российский кардиологический журнал, 2013)
This literature review focuses on the modern views on the problem of atherosclerotic plaque, its developmental stages (from the lipid steak to unstable atherosclerotic plaque), and various types of plaque instability (lipid, inflammatory, and degenerative-necrotic). Pathophysiologic (mechanisms of formation and development) and pathomorphologic (illustrated histologic description) characteristics of the process are also discussed.